Assessing acceptability of hypertensive/diabetic patients towards mobile health based behavioral interventions in Pakistan: A pilot study. Issue 11 (November 2015) - Siddiqui, Mahrukh; Islam, Mohammad Yousuf ul; Mufti, Bushra Abid Iqbal; Khan, Natasha; Farooq, Muhammad Saad; Muhammad, Mariam Gul; Osama, Muhammad; Kherani, Danish; Kazi, Abdul Nafey; Kazi, Abdul Momin
Highlights: Hypertension and Diabetes are rapidly growing chronic conditions in Pakistan with an increasing mortality rate due to poor knowledge, self-management and low quality of life. The potential positive and high scope of using Mobile Health services for management in chronic conditions like Diabetes and Hypertension in a developing country like Pakistan. The potential positive and high scope of phone call reminders against SMS reminders for self-management in Mobile Health services in Pakistan. Abstract: Introduction: Diabetes and hypertension are prevalent chronic diseases among the general population of Pakistan with an exponential progress expected over the upcoming years. Mobile Health services can be an efficient method of helping curtail this rise and improve quality of life of such patients as proven in developed countries. We aim to assess the acceptability of using Mobile Health services among diabetic and hypertensive patients in Pakistan. Methods: A total of 100 patients were approached in a large tertiary care Government Hospital of Karachi, Pakistan, using a nonprobability convenient sampling technique. Co-authors conducted an interview based sampling of a modified questionnaire to each participant after consent. All data was recorded and analyzed on SPSS 16. Results: A total of 100 patients participated in our study with 66 (66%) males and 34 (34%) females having a mean prevalence age of 54.27. All the 100 participants had easy access to cell phones with 88% participants (88/100) stating that they would be willing to participate in Mobile Health based interventions. A statistically significant number ( p = 0.014) of them preferred receiving phone calls (85.2%) rather than SMS (14.8%) reminders for these interventions. 85% of the participants even agreed to participate in such intervention on cash incentives. Conclusion: The use of phone call reminders or SMS reminders seems like an acceptable and favorable option among hypertensive and diabetic patients. This can greatly improve their self-management and help curtail this rise in the future.